Don Quijote, el escribidor y el escritor - Pollarolo, Giovanna (2010)
In his diverse critical studies, Mario Vargas Llosa has shown particular interest in reflecting on Miguel de Cervantes’s novelistic theory in accordance with his own concerns as a scholar and novelist. Suffice it to read the essay “Una novela para el siglo XXI” that he wrote in 2005 as an introduction to the edition of Don Quijote prepared to celebrate the IV Centenario, to make sure that Vargas Llosa “reads” Cervantes in accordance with his own reflections on the theory of the novel, fanaticism or the “insanity” of the characters, the fiction and its relationship with “reality”, the narrative voices or the problem of the narrator. But the Cervantes – Vargas Llosa relationship goes beyond the theoretical level or reflective and is manifested in his own novelistic creation such as ocurrs, specifically, in La tía Julia y el escribidor. In that sense, the main goal of this study is to analyze the “dialogue” that is set between La tía Julia y el escribidor and the Quijotefrom the point of view of the “insanity” of Pedro Camacho, the writer of radio soap operas created by Vargas Llosa, and their similarities with that of the knight-errant.